أثر الذكاء الاصطناعي على نشاط الضمان الاجتماعي - الصندوق الوطني للتأمينات الاجتماعية للعمال الاجراء وكالة المسيلة أنموذجا - - دمبري خليفة - زيان حسين (جامعة المسيلة, 2025)
The integration of artificial intelligence into the social security sector has become a necessary step to enhance service quality and improve the efficiency of file processing and service delivery for insured individuals. Among the most prominent digital tools that reflect this approach is the Chifa Card, which serves as a clear model for the application of artificial intelligence and the digitization of health services related to social security. This direction falls within the state's policy to modernize the social security sector, relying on legislative and regulatory frameworks that govern the use of modern technologies in the management of data and services—particularly considering the demands of AI systems in processing vast amounts of sensitive data, such as the health information package collected through the Chifa Card.
Keywords: : Artificial Intelligence; Social Security; Chifa Card; Socially Insured Person